KNOWLEDGE AND PRACTICES ABOUT PREVENTION AND TREATMENT OF BURNS IN THE HOME ENVIRONMENT (Estima – Brazilian Journal of Enterostomal Therapy, 2023)
Objectives: To analyze the knowledge and practices of individuals on the prevention and treatment of burns in the home environment and to describe the educational nursing care in the prevention and treatment of burns in the home environment. Method: Convergent Care Research (PCA) carried out virtually, from June to August 2021, with people residing in the city of Macaé/RJ. Results: The survey included 16 participants, 81.25% (n=13) female, aged between 19 and 59 years. In the analysis of the interviews, it was possible to identify mistaken knowledge and practices about the prevention and treatment of burns, to be discussed in this study. Conclusion: Although there is knowledge about the knowledge and practices on the prevention and treatment of burns in the home environment, there was identification of wrong practices that can harm the correct treatment and prevention of injuries. The findings of this study point to the need to build materials and carry out educational practices with this population to reinforce preventive measures for burns.